Perceptions of visitors toward post What About Kuching - Mohammad Azizul Syafiq, Abdullah; Shaik Azahar, Shaik Hussain
What About Kuching is a new event introduced to attract tourists from outside to Kuching. Therefore, researchers want to identify visitor awareness about this event. In addition, researchers want to study WAK as a platform that will promote the culture and the arts in Kuching. Finally, the researcher wanted to analyze the contribution of WAK to the local community. The researcher uses quantitative method in collecting data which is distribute questionnaire. The researcher found that there were not many visitors who knew about this event. However, they strongly agree that the event is capable of promoting Kuching and contributing to the local community.